Quality of Public Services in the Field of Population Administration in Paseh District, Bandung Regency - Risna Sari, Ade; Karim, Abdul (Prodi Administrasi Publik FISIP UNPAS, 2022)
The problem in this study is with the population administration services supplied by Paseh District, Bandung Regency. Where in the service process does it bring satisfaction to the community, and how does community satisfaction influence service quality in the field of population administration in Paseh District, Bandung Regency? This study seeks to define and analyse the quality of public services in the field of population administration in Paseh District, as well as to identify the factors that impede and support the implementation of public services in Paseh District, Bandung Regency. This study employs a qualitative descriptive research method. The data gathering methods used were observation, interviews, and documentation. To determine the quality of service in the field of population administration, apply Zeithaml et al.'s (1990: 19) service quality theory, which includes Tangible (tangible), Reliability (reliability), Responsiveness (responsiveness), Assurance (guarantee), and Emphaty (Empathy). This research's informants included the Head of the Government Section, the Secretary of the Subdistrict Head, employees, and the community. This research shows that the quality of services in the field of population administration in Paseh District, Bandung Regency is quite good but not yet optimal. This is caused by the existence of obstacles in the implementation of services that hinder the process of completing service products proposed by the community, and the incomplete facilities in the service rooms and the cleanliness of the room is not optimal, making people feel uncomfortable.